Physicochemical, nutritional and functional properties of Canarium odontophyllum (Dabai) - Ajibola, Olaide Olawunmi; Samuel, Lihan; Ahmad, Husaini (2022)
Dabai (Canarium odontophyllum) is commonly planted in most parts of the world and is highly rich in carbohydrates, carotenoids, vitamins, fat, protein, dietary fiber, and mineral and polyphenolic compounds. Some related studies have proven that dabai has the potential to induce anti-diabetic, anti-atherosclerotic, anticholinesterase and cardio protective effects. At the same time, it has attracted more attention in the medicinal as well as in the development of functional foods. These nutrient and bioactive compounds in dabai have significant effects on human health. In order to make better use of this crop, there is a need for further study. Therefore, the purpose of this article is to summarize the physicochemical properties and nutritional components of dabai, and to provide a reference for further research on the benefits to human health. Keywords: Canarium odontophyllum, Human health; Bio-functional property; Nutritional composition; Physicochemical property